2014
DOI: 10.1007/s00270-014-1023-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 3D Rotational Angiography on Liver Embolization Procedures: Review of Technique and Applications

Abstract: In the last years, the interest into interventional applications of C-arm cone-beam CT (CBCT) progressively raised, widening its clinical application from the original field of interventional neuroradiology to the field of peripheral procedures. Liver embolization procedures, due to their complexity and potential treatment-related life-threatening complications, represent one of the main clinical applications of this novel angiographic technique. CBCT has been demonstrated to render procedures safer and techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…However, unlike in DSA, in cone-beam CT, the skin dose of radiation is distributed over 180° of the body being imaged because of the rotational nature of the acquisition (17,18). Moreover, a single cone-beam CT examination can yield the same information as multiple DSA acquisitions in technically challenging cases, and may, therefore, reduce the total amount of radiation exposure, procedural time, and contrast medium use (19,21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, unlike in DSA, in cone-beam CT, the skin dose of radiation is distributed over 180° of the body being imaged because of the rotational nature of the acquisition (17,18). Moreover, a single cone-beam CT examination can yield the same information as multiple DSA acquisitions in technically challenging cases, and may, therefore, reduce the total amount of radiation exposure, procedural time, and contrast medium use (19,21).…”
Section: Discussionmentioning
confidence: 99%
“…Cone-beam CT has become popular for use in various interventional procedures such as adrenal vein sampling (27), transthoracic needle biopsy (28), transjugular intrahepatic portosystemic shunt procedure (29), and transcatheter arterial chemoembolization for hepatocellular carcinoma (16)(17)(18)(19). Bagla et al (15), in a recent publication about cone-beam CT before PAE, reported that cone-beam CT provided information that affected treatment in five of 11 (46%) patients by allowing for identification of sites of potential nontarget embolization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBCT consists in an angiographic unit equipped with a flat-panel detector that can provide volumetric tomographic images. Many authors proved that CBCT can be helpful in endovascular procedures (39)(40)(41). In vascular procedures, CBCT permits the assessment of complex vascular anatomy after a single injection of contrast medium in a targeted artery (38).…”
Section: Cone-beam Computed Tomography (Cbct)mentioning
confidence: 99%
“…However, literature shows that the major pivotal strength of CBCT, either mono-phasic or possibly bi-phasic, is the ability to depict in intra-procedurally ''occult lesions'', not visible at pre-procedural second-line non-invasive imaging (MRI, MDCT) [3]. This ability is not just for show, but yield to some major clinical implications: the visualization of an occult nodule identifies a subset of population experiencing fast tumour growth, having consequences on the number of adjunctive treatments controlling tumour growth (adjunctive RFA, or TACE procedures) and prioritization for transplantation [4]. Moreover, bi-phasic CBCT, with its unique ability to intra-procedural permit nodule characterization, could help in patients' reclassification and real-time TACE strategy modification [5].…”
Section: Dear Editormentioning
confidence: 99%